The influence of low physical activity levels versus extreme physical activity levels on brain structure and working memory - Paruk, Tasneem Yusuf (Department of Human Biology, 2021)
Background: Habitual levels of moderate to vigorous levels of physical activity (MVPA) levels are associated with positive health outcomes and improvement in cognitive function. A challenge facing optimal health outcomes is determining optimal levels of physical activity levels; people can engage in extreme sedentary or high levels of physical activity. For example, levels of low physical activity and participation in ultra-endurance events are increasing. However, the impact of extreme physical activity levels on brain matter volume and working memory is not well understood. This thesis thus investigated the relationship between different levels of MVPA, brain structure, and working memory. The aim of the thesis was to understand the relationship between large volumes of physical activity with global and regional brain matter volumes using brain imaging, and the impact of physical activity on cognitive function using the N-back task. The first part of the thesis examined how habitually high or low levels of MVPA differently impacted brain matter volume in healthy individuals. Whilst, the second part of the thesis investigated the differences in working memory between the low active and high active groups. Methods: Participants aged 20-59 years, were split into a High Activity (HA) group (N = 12, 27.9 ± 26.6 years) that exercised for > 9 hours of per week (MVPA > 540 minutes) and a Low Activity (LA) group (N = 9, 28.33 ± 11.192 years) that exercised < 2 hours (MVPA < 120 minutes). Total and regional brain matter volumes were measured using Magnetic Resonance Imaging (MRI) and analysed using Voxel-Based Morphometry (VBM). Habitual levels of physical activity were measured using the Global Physical Activity Questionnaire (GPAQ). For the second part of this thesis, we tested participants aged 20-59 years. Participants were split into a High Activity (HA) group (N = 6, 24.86 ± 4.67 years) that exercised for > 9 hours of per week (MVPA > 540 minutes) and a Low Activity (LA) group (N = 6, 30.14 ± 15.31 years) that exercised < 2 hours (MVPA < 120 minutes). Working memory was compared between the two groups using a PC-based N-back task. Results: The HA group had greater total brain matter and total white matter volumes vs. the LA group, and brain matter volumes were positively associated with increasing physical activity levels. However, the HA group had reduced regional brain volumes in the postcentral gyrus, middle frontal lobe, and the sub-lobar thalamus. HA and LA groups did not differ in working memory performance on the N-back task. Conclusion: Larger than normal amounts of weekly PA was associated with increased total brain matter and total white matter volumes, however, the volume of three regional brain areas were reduced.